Penguatan Peran Mahasiswa dalam Pemberdayaan Keagamaan dan Literasi Keuangan Syariah Umat di Kelurahan Kemlayan: Strengthening the Role of Students in Religious Empowerment and Sharia Financial Literacy of the Community in Kemlayan Subdistrict - Farras Rafi Niswara; Muhammad Latif Fazlullah Liansah; Gading Farrelio; Anugrah Vitra Fadian Afandi; Gilang Diptya Pradana; Ahmad Nurrohim (LITERA: Jurnal Ilmiah Mutidisiplin, 2025)
This community service program aimed to strengthen religious and financial literacy capacity through the Field Practice (PKL) activities of accounting students. The activities included teaching Qur’anic learning (TPA) every Saturday night, attending Sunday morning religious studies, recording zakat administrators, and assisting interest-free loan bookkeeping every Tuesday night. The participatory method was applied through direct observation and documentation. Results indicate improved participation in TPA, more systematic zakat records, and increased public awareness of sharia financial literacy. The findings highlight the potential role of students as change agents in community empowerment.